Bibliometric Analysis of Reverse Mentoring: A Global Perspective onResearch Trends and Developments (West Science Business and Management, 2025)
In the era of digital transformation and generational diversity in the workplace, reverse mentoring has become an important strategy in human resource management. This study aims to analyze the trends and development of research related to reverse mentoring globally using a bibliometric approach. Data was obtained from Google scholar with the keyword "reverse mentoring" and analyzed using the VOSviewer application to visualize the relationship between research elements. The analysis showed a significant increase in the number of publications since 2010, with the research focus shifting from general mentoring relationships towards professional development and leadership in the workplace. Key findings reveal that reverse mentoring and mentoring in general accelerate technology adoption, increase innovation, and strengthen cross-generational relationships within organizations. This study provides comprehensive insights into the contributions, dominant trends, and potential future research directions in the field of reverse mentoring.